Predictive value of plasma and peritoneal creatine kinase in horses with strangulating intestinal lesions. Issue 2 (26th December 2018) - Kilcoyne, Isabelle; Nieto, Jorge E.; Dechant, Julie E.
Abstract: Objective: To determine the ability of plasma and peritoneal creatine kinase (CK) to predict the presence of a strangulating lesion in horses presented for colic. Study design: Prospective clinical study. Animals: Ten healthy control horses and 61 clinical colic cases. Methods: Creatine kinase activity was measured in peritoneal fluid and plasma of 10 healthy horses and 61 horses presenting for colic (40 horses with nonstrangulating lesions and 21 horses with strangulating lesions). Information on other blood and peritoneal fluid variables, signalment, results from the physical examination, outcome, requirement for surgery, and lesion location and type were retrieved from the medical records of horses presenting for colic. Results: A peritoneal CK cutoff level of 16 IU/L yielded a sensitivity of 95.2% and a specificity of 84.6% (positive predictive value [PPV] = 76.9% and negative predictive value [NPV] = 97%, respectively) for predicting a strangulating lesion. A peritoneal lactate cutoff level of 3.75 mmol/L yielded a sensitivity of 81% and a specificity of 92% (PPV = 85% and NPV = 90%, respectively) for predicting a strangulating lesion. Conclusion: Peritoneal CK concentration was a sensitive indicator of the presence of a strangulating lesion in horses presenting with colic, whereas peritoneal lactate concentration was a more specific indicator. Clinical significance: Measuring CK in peritoneal fluid may be a useful adjunct to clinical case presentation to accelerate the diagnosis and definitive treatment of horses presenting with strangulating intestinal lesions, thereby improving their outcome.